The Attitude of Student Youth in the South of Russia to the 2021 Population Census - Galina S. Denisova (Регионология, 2022)
Introduction. A census is a necessary tool of managing a modern state. IT penetration into all spheres of life caused digitalization of census, the procedure which rests on consciousness and is voluntary in its nature. Transition to these technologies is related to a number of difficulties influencing the quality of census. The goal of the article is to identify the attitude of the south Russian students’ youth to participation in census, its optimal forms and the aspects causing major concerns among this target group.